2004
DOI: 10.1101/gr.1949704
|View full text |Cite
|
Sign up to set email alerts
|

Two Methods of Whole-Genome Amplification Enable Accurate Genotyping Across a 2320-SNP Linkage Panel

Abstract: Comprehensive genome scans involving many thousands of SNP assays will require significant amounts of genomic DNA from each sample. We report two successful methods for amplifying whole-genomic DNA prior to SNP analysis, multiple displacement amplification, and OmniPlex technology. We determined the coverage of amplification by analyzing a SNP linkage marker set that contained 2320 SNP markers spread across the genome at an average distance of 2.5 cM. We observed a concordance of >99.8% in genotyping results f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
130
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(138 citation statements)
references
References 24 publications
(36 reference statements)
7
130
0
Order By: Relevance
“…Lastly, new technologies are emerging that may overcome limitations of the current methodology. For example, random hexamer priming and terminal transferase end-labeling 33,34 may enhance cDNA synthesis, a troublesome step in the current approach. It is reasonable to believe these approaches may improve cDNA synthesis over methods relying on traditional oligo-dT primer as polyA tracts seem particularly prone to formalin-mediated covalent modification.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, new technologies are emerging that may overcome limitations of the current methodology. For example, random hexamer priming and terminal transferase end-labeling 33,34 may enhance cDNA synthesis, a troublesome step in the current approach. It is reasonable to believe these approaches may improve cDNA synthesis over methods relying on traditional oligo-dT primer as polyA tracts seem particularly prone to formalin-mediated covalent modification.…”
Section: Discussionmentioning
confidence: 99%
“…Whole genome amplification of genomic DNA was performed before genotyping of the initial dataset using the GenomiPhi Amplification Kit (GE Healthcare, Little Chalfont, UK). 46 Single nucleotide polymorphisms with a genotype success rate o80% in the initial data set, MAFo0.05 or with unreliable genotype calling, were omitted, leaving 137 SNPs, in Hardy-Weinberg equilibrium, for statistical analyses. The average distance between the SNPs was 14 kb on the basis of the UCSC Genome Browser, May 2004 assembly (http://genome.ucsc.edu/).…”
Section: Genotypingmentioning
confidence: 99%
“…It has been used successfully by other groups, and has shown no detectable locus or allele bias. 21,22 We found that this method worked well for amplifying DNA from archival formalin-fixed, paraffin-embedded samples. Whole genome amplified DNA was purified using the Qiagen MinElute PCR purification kit (Qiagen), prior to LOH analysis.…”
Section: Whole Genome Amplificationmentioning
confidence: 99%